Environmental Effects on Parental Care Visitation Patterns in Blue Tits Cyanistes caeruleus - Lejeune, Léa; Savage, James L.; Bründl, Aisha C.; Thiney, Alice; Russell, Andrew F.; Chaine, Alexis S. (Frontiers in Ecology and Evolution, 2019)
In bi-parental systems each parent shares benefits with its unrelated partner from the common investment in offspring, but pays an individual cost of providing that care in terms of reduced survival or fecundity, leading to sexual conflict. However, several recent empirical studies have shown that coordinating behaviours like synchronisation (e.g. arriving at similar times) and alternation (taking turns in providing care) at the nest lead to increased investment overall, presumably to reduce conflict through policing or synergistic benefits. Ecological conditions should impact the costs and benefits of bi-parental care, yet there exists a gap in research on the relationship between ecological conditions and patterns of parental care behaviour beyond visitation rate. Here we provide an examination of how bi-parental provisioning behaviours, i.e. pair feeding rate and feeding consistency, and the degree to which parents synchronise or take turns, differ under contrasting ecological conditions in populations of blue tits (Cyanistes caeruleus) spanning a 1000m altitudinal gradient. We found that blue tits pairs synchronised and alternated more than expected by chance, and that care patterns were modified by ecology. Pairs synchronised more in woodland-pasture edges than in woodland interiors, and alternated more and fed more frequently at low altitude compared to higher altitude nests. Variation in bi-parental coordination behaviours did not have a significant impact on fledging success but more synchronous nests had heavier chicks in woodland habitats. Taken as a whole, our results show that patterns of care are influenced by ecological conditions and that their interplay may change the outcome of sexual conflict.